Community-Focused Language Documentation in Support of Language Education and Revitalization for St. Lawrence Island Yupik - Schwartz, Lane; Schreiner, Sylvia; Chen, Emily (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2019)
St. Lawrence Island Yupik, an endangered language of the Bering Strait region spoken by fewer than one thousand people in western Alaska and far eastern Russia, is currently in a state of generational transition. We survey the existing body of Yupik literature and pedagogical resources developed during the twentieth century, examine the context and use of Yupik in the current educational setting, and describe current challenges for teaching the language in the schools. We then outline our integrated approach to language documentation currently being applied to Yupik, and address how existing resources can be integrated into research and development processes in a way that both supports research efforts and results in tangible modern educational tools for the Yupik community on St. Lawrence Island, and eventually in Russia. This approach is intentionally designed to closely integrate research processes from language documentation and computational linguistics such that the results of each research endeavour positively support the other, and such that both disciplines concretely support community-based efforts to revitalize and teach the language.